Socio-demographic Characteristics and Clinical Profiles of Women Presented with Post-Caesarean Section Complications - Sharmin, Nazrana; Begum, Asma; Afreen, Sadia; Akhter, Jafrin; Akter, Ayenun; Ferdousi, Qazi Hena (Journal of Current and Advance Medical Research, 2024)
Background: Post-caesarean section complications can occur in different Socio-demographic Characteristics with varied clinical profiles. Objective: The purpose of the present study was to see the socio-demographic characteristics and clinical profiles of women presented with post-caesarean section complications. Methodology: This cross-sectional study was conducted in the Department of Obstetrics and Gynaecological at Dhaka Medical College and Hospital, Dhaka, Bangladesh from January 2013 to June 2013 for a period of six months. All women admitted with post caesarean section complications referred from different level of hospitals with the age group of more than or equal to 18 years were included as study population. All relevant data were recorded in a predesigned data collection sheet which included age, social status, economic condition and parity. Results: A total number of 50 women who were underwent caesarean section outside DMCH and admitted with post-caesarean section complications were included in this study. Maximum (40.0%) patients were within the age group of 21 to 25 years. Majority of the patients completed their primary and secondary level of education which was 16(32.0%) cases and 18(36.0%) cases respectively. Majority (56.0%) were multiparous. Primi was found in 20(40.0%) cases. Conclusion: In conclusion most the women are in younger age group with secondary and higher secondary education. Journal of Current and Advance Medical Research, July 2023;10(2):49-52